Forensic Turn and Contemporary Central American Novel - Rivera Rivera, Rónald (2025)
An analysis is presented of an aesthetic trend in contemporary Central American narrative. Using the so-called forensic turn, several literary productions addressing, in their fictions, the exercise of violence in the recent past of Central America are studied with the purpose of constructing a truth based on the material evidence of these events. The documentary attitude of these fictions takes shape in a preeminence of documents and police files, rather than victim testimony, as an alternative way of revealing the violence and crimes perpetrated by those in power.